2019
DOI: 10.1186/s12863-018-0712-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for paternal DNA transmission to gynogenetic grass carp

Abstract: BackgroundGrass carp (Ctenopharyngodon idellus, GC), as the highest-output fish in China, is economically important. The production of gynogenetic grass carp (GGC) will provide important germplasm resource for producing improved GC. At present, knowledge regarding the heterologous sperm DNA in gynogenetic offspring is little. Thus, revealing paternal DNA in GGC at the molecular level would be highly significant for fish genetic breeding.ResultIn this study, ultraviolet-treated sperm of koi carp (Cyprinus carpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In studies of androgenetic rainbow trout, maternal chromosomal fragments were found in karyotyped-treated offspring (Ocalewicz et al, 2004). Paternally derived markers were found in treated offspring of gynogenetic grass carp (Ctenopharyngodon idellus) using microsatellites (Mao et al, 2019), and in gynogenetic gibel carp (Carassius gibelio)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of androgenetic rainbow trout, maternal chromosomal fragments were found in karyotyped-treated offspring (Ocalewicz et al, 2004). Paternally derived markers were found in treated offspring of gynogenetic grass carp (Ctenopharyngodon idellus) using microsatellites (Mao et al, 2019), and in gynogenetic gibel carp (Carassius gibelio)…”
Section: Discussionmentioning
confidence: 99%
“…In studies of androgenetic rainbow trout, maternal chromosomal fragments were found in karyotyped‐treated offspring (Ocalewicz et al ., 2004). Paternally derived markers were found in treated offspring of gynogenetic grass carp ( Ctenopharyngodon idellus ) using microsatellites (Mao et al ., 2019), and in gynogenetic gibel carp ( Carassius gibelio ) using PCR primers specific to the paternal donor and subsequent amplicon sequencing (Chen et al ., 2020; Yi et al ., 2003). The diversity of findings of these studies highlights a benefit of using genome‐wide approaches that enable assignment of alleles and haplotypes to the parents, particularly the male, as the authors have done here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation